A Comparison of Essential Oil and Organic Acid Supplementation on the Live Performance and Intestinal Morphology of Broilers Fed a Diet Containing Palm Kernel Meal - Phuengkasem, A.; Attamangkune, S.; Ruangpanit , Y. (International Journal of Poultry Science, 2017)
Background and Objective: Non-Starch Polysaccharides (NSPs) are indigestible substances found in plant cell walls. Typically, they trap nutrients, increase the viscosity of intestinal contents and decrease the passage rate of the digesta. That condition is favorable for bacterial growth and can negatively affect bird health. The objective of this study was to compare the antimicrobial effects of commercial Essential Oil (EO) and Organic Acid (OA) supplementation and their effects on the growth performance and intestinal morphology of broilers fed a corn-soybean-based diet containing Palm Kernel Meal (PKM). Materials and Methods: The experiment was conducted using a completely randomized design. A total of 1,152, one-day-old broiler chicks (Ross 308) were divided into 6 dietary treatments: C (control), N (negative control), C+EO, C+OA, N+EO and N+OA. Each treatment consisted of 8 replicates with 24 chicks per replicate (12 males and 12 females). All chicks were raised in an evaporative cooling system house with rice husk as the litter material. Feed in mash form and water were provided ad libitum. Results: Supplementation with EO and OA had no significant effect on the growth performance of the broilers throughout the experimental period (p>0.05). There was no significant difference in the Escherichia coli and Lactobacillus spp. populations in the ceca of the broilers at 17 and 35 days of age (DOA) (p>0.05). Similar results were observed for ileal crypt depth and villi surface area between the dietary treatments. Conclusion: Supplementation with EO and OA at 30 and 2,000 ppm, respectively, had no significant effect on broilers’ growth performance, ceca populations of Escherichia coli and Lactobacillus spp. and gut health.